Host specificity, pathogenicity, and mixed infections of trypanoplasms from freshwater fishes - Losev, Alexander; Grybchuk-Ieremenko, Anastasiia; Kostygov, Alexei Yu; Lukeš, Julius; Yurchenko, Vyacheslav (Parasitology research, 2015)
This work summarizes the results of the 8-year study focused on Trypanoplasma sp. parasitizing freshwater fishes in the vicinity of Kyiv, Ukraine. Out of 570 fish specimens of 2 different species analyzed, 440 individuals were found to be infected. The prevalence of infection ranged from 24 % in Abramis brama Linnaeus (freshwater bream) to 100 % in Cobitis taenia Linnaeus (spined loach). The level of parasitemia also varied between moderate in freshwater bream and very high in spined loach. Interestingly, no clinical manifestations of trypanoplasmosis were observed even in extremely heavily infected C. taenia. We hypothesize that different species may differ in evolutionary timing allowing for reciprocal adaptation of the members of the "host-parasite" system. Molecular analysis of the 18S rRNA sequences revealed that several specimens were simultaneously infected with at least two different trypanoplasm species. To the best of our knowledge, this is the first report of the mixed infection with fish trypanoplasms.
Keywords: Fresh Water; Prevalence; Ukrajina; prevalence; sladká voda; Ukraine; zvířata; Kinetoplastida; Host Specificity; nemoci ryb; Euglenozoa Infections; koinfekce; Fish Diseases; Fishes; Coinfection; infekce prvoky kmene Euglenozoa; ryby; hostitelská specificita; Animals